OP0233 Frequency and Predictive Variables of Relapses in Patients with Biopsy-Proven Giant Cell Arteritis. (9th June 2015) - Restuccia, G.; Boiardi, L.; Muratore, F.; Cavazza, A.; Cimino, L.; Aldigeri, R.; Macchioni, P.; Catanoso, M.G.; Pipitone, N.; Salvarani, C.
Abstract : Background: Giant cell arteritis (GCA) is a vasculitis that involves large and medium sized arteries in patients older than 50 years. Relapses and recurrences of the disease have been reported in 40.8–48% of patients, leading to longer duration of glucocorticoids (GCs) therapy and to increased risk of GCs side effects. Objectives: The aim of our study was to determine the frequency and the predictors of disease relapses in a large monocentric cohort of consecutive patients with biopsy- proven GCA. Methods: All patients with a diagnosis of biopsy-proven GCA made at our centre between 1986 and 2007 were identified. Only patients with a follow-up period longer than 6 months were included in the study. A pathologist with expertise in vasculitis reviewed all temporal artery biopsies (TABs). Demographic, clinical and laboratory data at presentation and at each follow-up visit were retrospectively collected. Relapse was defined as recurrences of symptoms with rise in inflammatory markers during tapering of GCs or after GCs discontinuation. Results: 181 patients had a diagnosis of biopsy-proven GCA in the study period. 22 patients had a follow-up shorter then 6 months, and were excluded from further analyses. Median (Q1, Q3) follow-up period for the 159 patients included was 80 (49, 125) months. 57/159 (35.8%) patients relapsed during the follow-up period, with a median of 1 (range: 1–7) relapses. Most common clinical manifestation at first relapse was polymyalgia rheumatica (44%), followed by headache (37%). Only 1 patient developed visual loss secondary to disease relapse. Mean (DS) prednisone dose at the time of first relapse was 6.3 (10.1) mg/day. At univariate analysis predictors of relapses were the levels of hemoglobin (Hb) (HR 0.793, p=0.037), fever (HR 1.938, p=0.029), presence of giant cells (HR 2.560, p=0.031), acute thrombosis (HR 2.805, p=0.003), and a more severe inflammation on a semiquantitative scale (HR 3.973, p=0.011 for moderate inflammation; HR 3.051, p=0.039 for severe inflammation) at TAB. Furthermore total duration of corticosteroid therapy [mean (SD) 64 (46) vs 31 (32) months, p=0.0001] and cumulative dose of prednisone [mean (SD) 16.7 (12.3) vs 9.7 (9.2) grms, p=0.0001) were significantly higher in patients whit disease relapses than in those without. Multivariate analysis confirmed as independent predictors of relapses the levels of Hb, [HR (CI 95%) 0.738 (0.575–0.947), p=0.017], the presence of moderate and severe inflammation at TAB [HR (CI 95%) 4.648 (1.328–16.363), p=0.016; and 3.653 (1.085–12.302), p=0.037 respectively for moderate and severe inflammation] and the presence of acute thrombosis at TAB [HR (CI 95%) 2.29 (0.974–5.383), p=0.05]. Conclusions: The results of the present study confirm that relapses are frequent in patients with biopsy-proven GCA. The levels of hemoglobin at diagnosis, the severity of inflammation and the presence of acute thrombosis at TAB are independent predictors of disease relapses. Disclosure of Interest: None declared